(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
There has been examined the effect of changing the motion law of piston in a differential mortar pump on the amount of lossesof construction mortar mix of the injectionvalve which operates at closing. Keywords:differential mortar pump, piston, the law of motion, valve.